Sacral Fracture Nonunion Treated by Bone Grafting through a Posterior Approach - Sang Yang Lee; Takahiro Niikura; Yoshitada Sakai; Masahiko Miwa; Kotaro Nishida; Ryosuke Kuroda; Masahiro Kurosaka (Case Reports in Orthopedics)
Nonunion of a sacral fracture is a rare but serious clinical condition which can cause severe chronic pain, discomfort while sitting, and significant restriction of the level of activities. Fracture nonunions reportedly occur most often after nonoperative initial treatment or inappropriate operative treatment. We report a case of fracture nonunion of the sacrum and pubic rami that resulted from non-operative initial treatment, which was treated successfully using bone grafting through a posterior approach and CT-guided percutaneous iliosacral screw fixation combined with anterior external fixation. Although autologous bone grafting has been the gold standard for the treatment of pelvic fracture nonunions, little has been written describing the approach. We utilized a posterior approach for bone grafting, which could allow direct visualization of the nonunion site and preclude nerve root injury. By this procedure, we were able to obtain the healing of fracture nonunion, leading to pain relief and functional recovery.